Effects of photoperiod on reproduction of cattle: a review. Issue 12 (2nd December 2022) - Pal, Prasanna; Aggarwal, Anjali; Deb, Rajib
ABSTRACT: A photoperiod is the time duration when animals are exposed to light in an entire day. An exposure of 16 hours or more is considered a long-day photoperiod and 8 hours of light is a short-day photoperiod. Exposure to light prevents the secretion of melatonin from the pineal gland. Melatonin can influence the release of several hormones, including prolactin, cortisol, kisspeptin, GnRH and others. Eventually, it can also affect the reproductive performance of the animal. Though cattle are not a seasonal breeder, photoperiod has an indirect role in the onset of puberty, pregnancy and parturition. It can also promote the growth rate of the heifers and enhance their reproductive capabilities, which are very much desired by the producers. Therefore, photoperiod can be used as an effective and non-invasive tool in the reproductive management of cattle.